Pengaruh Pemahaman Sistem Akuntansi, Pengelolaan Keuangan, Kapasitas Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan - Setyobudi Setyobudi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to understand the financial accounting system and financial management, the capacity of human resources partially or simultaneously influences the quality of information on the financial statements of the local government of Pati Regency. The sampling technique used was purposive sampling. Respondents sampled in this study, namely employees who work at the Pati Regency SKPD environmental service in the 2021 financial report, bear the WTP predicate six times from the BPK. In this study, certain criteria were used, namely employees of the finance department, having a minimum education level of high school/equivalent and having worked for at least 1 year. The types of data used in this study are primary and secondary data. The primary data in this study were the respondents' answers to the questionnaires distributed. Secondary data in this study is the organizational structure, and an explanation or general description of the organization as well as data on the number of employees in the finance department in each department. Testing the data is done by testing the validity and reliability test, multicollinearity test, and heteroscedasticity test, while hypothesis testing with multiple regression analysis using the SMART PLS program.3. The results showed that both partially and simultaneously Understanding of Regional Financial Accounting Systems, Regional Financial Management, and Human Resource Capacity had a positive and significant effect on the Quality of Information on Local Government Financial Reports